Permeability Barrier Methods and Protocols - Turksen, Kursad.; Turksen, Kursad. (Methods in Molecular Biology,, 2011)
The significant biological subject, the permeability barrier, is incredibly diverse and vital for a vast assortment of crucial functions in the body.  In Permeability Barrier: Methods and Protocols, a variety of experienced researchers contribute techniques to study this complex system in its many forms.  Written in the highly successful Methods in Molecular Biology™ series format, chapters include brief introductions to their respective topics, detailed lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.   Authoritative and practical, Permeability Barrier: Methods and Protocols serves as an ideal guide for all scientists seeking to further our understanding of this vital area of research.